Modelling of Ethane/Ethylene Separation Using Microporous - Susana Curbelo; Erich A. Müller (Adsorption Science & Technology)
Grand Canonical Monte Carlo simulations of the adsorption of a mixture of ethane and ethylene on microporous slit graphite pores are reported. A two-centre Lennard-Jones with point quadrupole potential and a Steele potential with embedded quadrupoles for the carbon were used to model the fluids and solids, respectively. Under conditions of moderate temperature (260–400 K) and pressure (0.1–1.0 MPa), ethane was preferentially adsorbed over ethylene for the pore widths studied. For micropores less than 2 nm wide, the selectivity towards ethane varied markedly with small changes in the pore structure, whilst for the mesopores with widths greater than 2 nm the selectivity was remarkably insensitive towards the pore size. The results provide qualitative guidelines for the synthesis and design of carbons for lower olefin/paraffin separations.